Operations of Street Food Vendors and Their Impact on Sustainable Urban Life in High Density Suburbs of Harare, in Zimbabwe - Njaya, Tavonga (Asian Journal of Economic Modelling, 2014)
The study sought to investigate the nature and operations of street food vendors including socio-economic features influencing street food vending spatial distribution and its impact on the local environment and urban life within the context of sustainable development. Data were collected through field notes, in-depth personal interviews, direct observations and documentary reviews so as to triangulate the evidence. Sixty semi-structured questionnaires were administered to collect socio-economic and technical data pertaining to street food vending. The study showed that street food vending, far from being a hindrance to progress and sustainable development, is in fact the basis of an alternative street economy which is people friendly and with the necessary institutional and infrastructural support could be both environmental-sensitive and energy conscious. Although street food vending is illegal, it significantly helped to reduce unemployment, increased incomes of vendors and provided urban dwellers with inexpensive and varied indigenous meals. The government should recognise street food industry through legislation and introduction of a code of practice for street food vendors. This would require city council to construct decent shelters and provide essential public utilities such as potable water, electricity and public toilets. What is needed to advance the position of street food vendors is to strengthen their capacities and skills through training, credit, information and infrastructure so as to enhance their competitiveness and productivity. There is need for further research to describe the nature of street vending and quantify the consumption of street foods in Zimbabwe and their economic benefits as well as ways to improve the standards of street food.